1997
DOI: 10.18474/0749-8004-32.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Lady Beetles (Coleoptera: Coccinellidae) in Sweet Corn Using Yellow Sticky Cards

Abstract: Yellow cards coated with adhesive were used to survey for the presence, relative abundance and seasonal patterns of lady beetles in research and commercial fields of processing sweet corn in central and western New York in 1992 and 1993. The lady beetles species recorded, in order of abundance were: Coleomegilla maculata lengi Timberlake, Coccinella septempunctata L., Psyllobora vigintimaculata (Say), Hippodamia parenthesis (Say), Propylea quatuordecimpunctata (L.), Cycloneda munda (Say), Hippodamia glacialis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Clearly, a dearth in the scientiÞc literature addressing the mycophagy exhibited by these insects has led to some biological inaccuracies. The cosmopolitan genus Psyllobora Chevrolat is represented in temperate and subtropical regions worldwide, in natural and managed systems, and contains a group of insects with the potential to provide biological control of PM (Prasad and Rai 1988, Cruz et al 1989, Hoffman et al 1997, Almeida and Milleo 1998, Tezcan and Uygun 2003. Soylu et al (2002) recorded a reduction in PM conidia of 92% by comparing leaf areas grazed upon by P. bisoctonotata Mulsant with nonfed-upon areas, suggesting a real and measurable PM removal through consumption.…”
mentioning
confidence: 99%
“…Clearly, a dearth in the scientiÞc literature addressing the mycophagy exhibited by these insects has led to some biological inaccuracies. The cosmopolitan genus Psyllobora Chevrolat is represented in temperate and subtropical regions worldwide, in natural and managed systems, and contains a group of insects with the potential to provide biological control of PM (Prasad and Rai 1988, Cruz et al 1989, Hoffman et al 1997, Almeida and Milleo 1998, Tezcan and Uygun 2003. Soylu et al (2002) recorded a reduction in PM conidia of 92% by comparing leaf areas grazed upon by P. bisoctonotata Mulsant with nonfed-upon areas, suggesting a real and measurable PM removal through consumption.…”
mentioning
confidence: 99%
“…Biological control agents may be helpful if they would control both the adults and hidden stages, but information on biocontrol of ulidiid flies is lacking. Major predators of sweet corn pests in the northeastern United States are Coleomegilla maculata (DeGeer), Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), and Orius insidiosus (Say) (Hemiptera: Anthocoridae) (Andow & Risch 1985;Coll & Bottrell 1992;Coderre et al 1995;Wheeler & Stoops 1996;Hoffmann et al 1997;Musser et al 2004). In Mexico, the wasps, Spalangia spp.…”
mentioning
confidence: 99%
“…Based on previous survey work in the northeastern United States (Whitman 1975, Andow and Risch 1985, Coll and Bottrell 1992, Hoffmann et al 1997, the primary predators in sweet corn were expected to be coccinellids, especially Coleomegilla maculata (De Geer), and the anthocorid Orius insidiosus (Say). Another coccinellid, Harmonia axyridis (Pallas), has entered the area since these surveys (Coderre et al 1995, Wheeler andStoops 1996) and has been found in sweet corn Þelds (Musser 2003).…”
mentioning
confidence: 99%
“…There are several reports on estimating populations of coccinellids in sweet corn by using sticky cards (Ewert and Chiang 1966, Hoffmann et al 1997, Bruck and Lewis 1998, Colunga-Garcia and Gage 1998, a modiÞed leaf blower (Beerwinkle et al 1999), and visual Þeld counts (Foott 1973, Nault and Kennedy 2000, Wold et al 2001. In grain sorghum, a crop with a plant structure similar to corn, Michels and Behle (1992) found that visual counting had less bias than drop cloths, sweep nets, or pit traps for coccinellid adults.…”
mentioning
confidence: 99%